Proceedings of the 2015 ACM Conference on Special Interest Group on Data Communication 2015
DOI: 10.1145/2785956.2787495
|View full text |Cite
|
Sign up to set email alerts
|

A Declarative and Expressive Approach to Control Forwarding Paths in Carrier-Grade Networks

Abstract: SDN simplifies network management by relying on declarativity (high-level interface) and expressiveness (network flexibility). We propose a solution to support those features while preserving high robustness and scalability as needed in carrier-grade networks. Our solution is based on (i) a two-layer architecture separating connectivity and optimization tasks; and (ii) a centralized optimizer called DEFO, which translates high-level goals expressed almost in natural language into compliant network configuratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
109
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(109 citation statements)
references
References 47 publications
0
109
0
Order By: Relevance
“…Table 2 summarizes the real ISP and enterprise network topologies we evaluated and the size of end-toend traffic demands placed into each network. We evaluated six real-world ISP topologies, labeled ISP1 through ISP6, using traffic demands [16] that are publicly available at [2]. The enterprise network topology, ENTR, is parsed from router configurations of a real campus network [22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 summarizes the real ISP and enterprise network topologies we evaluated and the size of end-toend traffic demands placed into each network. We evaluated six real-world ISP topologies, labeled ISP1 through ISP6, using traffic demands [16] that are publicly available at [2]. The enterprise network topology, ENTR, is parsed from router configurations of a real campus network [22].…”
Section: Methodsmentioning
confidence: 99%
“…Besides, with injected "lies", Fibbing could lead to debugging issues and incorrect operation. DEFO [16] leverages segment routing to control routing paths for carrier-grade traffic engineering, but shares some similar limitations as in Fibbing. Besides, its constraint programming based middle-point selection largely focuses on static traffic matrices, while our proposed TE module can load balance dynamic traffic demands.…”
Section: Related Workmentioning
confidence: 99%
“…Several limitations of this approach have been identified. First, these rules grow with the number of flows, policies and chains' size, while forwarding state on network appliance is limited by costly memory [9]. Second, they grow in complexity when a vSF make a hard to handle change in network headers (e.g., Network Address Translation service) [7], [8], [10].…”
Section: Related Workmentioning
confidence: 99%
“…By simulating the centralized controller approach on many operator use cases, we observed that the number of SR TE tunnels to be injected to comply with SLA constraints, and re-optimization of such tunnels during failures, led to much less signaling overhead when compared to the distributed RSVP-TE based approach. [13] reports reductions of up to an order of magnitude in the state maintained in routers for 10 different topologies by using SR instead of RSVP-TE. Furthermore, studies have shown that only a few segments are required to obtain optimal traffic distributions: [13] obtains traffic distribution close to the ones of RSVP-TE using only 2 labels.…”
Section: A Traffic Engineering Using Sr Tunnelsmentioning
confidence: 99%
“…[13] reports reductions of up to an order of magnitude in the state maintained in routers for 10 different topologies by using SR instead of RSVP-TE. Furthermore, studies have shown that only a few segments are required to obtain optimal traffic distributions: [13] obtains traffic distribution close to the ones of RSVP-TE using only 2 labels. Independently, [14] also informs that two segments were required to achieve solutions close to the theoretically optimal ones.…”
Section: A Traffic Engineering Using Sr Tunnelsmentioning
confidence: 99%